A report of 3 cases of Exeter V40 Stem fracture and explanation of possible causes. Issue 6 (November 2018) - Garala, Kanai; Laios, Thomas; Lawrence, Trevor
Background: The Exeter V40 Orthinox stem is one of the most commonly used femoral components in total hip arthroplasty. Its design, material and finish has evolved significantly from the original design established by Ling and Lee over 3 decades ago. An early problem reported with the original Exeter stem was a high rate of stem fractures. It was thought that with the new Orthinox steel used in the V40 system, the rate of stem fractures would reduce. There are reports of the Exeter V40 stem failing in a variety of locations. Cases: This paper highlights the 3 locations where the Exeter stem may fail and estimates a rate of 0.262% for stem fractures due to the constant use of the Exeter stem throughout the career of the senior surgeon.